TECHNOLOGIES OF SORPTION WASTEWATER TREATMENT: EXPERIENCE OF USE AND INNOVATION - Mazurak О.; Lysak Г.; Zelisko О.; Hrynchyshyn Н.; Mazurak І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The article presents research results on the use of various types of sorbents, including natural silicate minerals and their modified forms, as well as biosorbents based on waste, to purify wastewater from pollutant ions. The researchers provide examples of naturally occurring mineral sorbents and biosorbents, their selectivity for pollutants, and their advantages and disadvantages. They argue that further research into new sorption and biosorption technologies is necessary as these are the most effective methods of cleaning man-made waters in terms of both economic indicators and cleaning efficiency. The article also describes the properties of natural modified sorbents of various origins, including their binding mechanisms for pollutant ions, such as heavy metals. Modern methods of analysis, such as infrared spectroscopy (FT-IR), photoelectron spectroscopy, X-ray absorption spectroscopy (XAS), scanning electron microscopy (SEM), nuclear magnetic resonance (NMR) and energy dispersive X-ray spectroscopy (EDS) are used to establish these mechanisms. The article also highlights the advantages of modern physicochemical methods, particularly X-ray absorption spectroscopy, as a powerful tool for evaluating the binding mechanisms of various biomaterials. The researchers studied the possibilities of valorizing organic waste produced by agro-industrial and other industries to develop innovative complex technologies using biosorbents for wastewater treatment. These technologies offer prospects for large-scale implementation. The article concludes by proving the effectiveness of combining sorption and other technologies to purify wastewater from pollutants of various origins. The researchers also stress the importance of finding new, cheap, and effective sorption materials to optimize the quality of water bodies in the environment, in accordance with the principles of sustainable development.